PEMODELAN PADA STABILITAS LERENG DENGAN PERKUATAN GEOGRID MENGGUNAKAN SOFTWARE GEOSLOPE - Naufal Hammam (Jurnal Vokasi Teknik Sipil, 2024)
The Geoslope software is a tool designed for analyzing slope stability and risk assessment, particularly in geotechnical engineering. With the advancement of this technology, it facilitates and expedites the calculation process. The analysis results of slope stability without reinforcement using the Bishop method, based on data from Standard Penetration Test (SPT), indicate a value of 0.746 in the Geoslope software. According to Bowles (1984) classification, this slope is in a critical condition or prone to landslide. The solution to address this issue is by adding reinforcement to the slope, using geogrid with a tensile strength of 40 kN/m. The geogrid is installed with a length of 12 meters on slope 1 and 8 meters on slope 2, with a vertical spacing between geogrids of 0.5 meters. The analysis results after reinforcement show an increase in value to 1.314, indicating that the slope is now in a safe or stable condition.